National Microbiological Laboratory Reporting Service - Bulletin 8. 8-21 April 1977 - whole issue - No author listed (Communicable Diseases Intelligence, 1977)
Whole-issue pdf, comprising: Explanation of abbreviations used in tables Laboratory Codes: ICPMR - Institute of Clinical Pathology and Medical Research, Lidcombe RAHC - Royal Alexander Hospital for Children, Camperdown PHH/POW - Prince Henry/Prince of Wales Hospital Group, Sydney FAIRFIELD - Fairfield Hospital [Melbourne] RCH - Royal Children's Hospital, Parkville IMVS - Institute of Medical and Veterinary Science, Adelaide STATE LAB - State Health Laboratory Services, Perth Specimen Codes: FA - faeces/rectal swab BL - blood/serum NA - nasopharyngeal swab or aspirate CS - cerebrospinal fluid SK - skin EY - eye UR - urine BR - bronchial washings or aspirate GE - genital swab OT - other Article Outbreak of diarrhoea in neonates. [Melbourne, Vic.] [further report in Bulletin 10] Para-influenza virus type 2. [Melbourne, Vic.] Hepatitis B in Adelaide Food poisoning on international aircraft due to non-cholera vibrio National Microbiological Laboratory Reporting Service - Period 8 8-21 April 1977